ANALYSIS OF THE RESULTS OF THE PARTICIPATING COUNTRIES' PERFORMANCES AT THE 2024 OLYMPIC GAMES IN JUDO (Physical Culture and Sport: Scientific Perspective, 2024)
The article analyzes the results of the participating countries' performances at the 2024 Olympic Games in judo. It is established that athletes from 5 continents and 122 countries took part in the Olympic Games in Judo, the total number of participants is 378, including 192 men and 186 women. Moreover, the largest number of participants are representatives of the European Judo Union - 180 participants, and the Asian Judo Union - 95 participants, which is explained by the popularity of judo in the respective countries of the Union, the availability of appropriate funding for representatives and the number of nations that are representatives of the Union. The analysis of the number of participants in weight categories at the 2024 Olympic Games in judo showed that the number of athletes in weight categories averaged 27 for both men and women. The largest number of participants was among men in the 81 kg weight category, and 31 among women in the 48 kg weight category. The results of the medal standings of the participating countries at the 2024 Olympic Games in judo showed that the leaders of the competition are such countries as Japan, Azerbaijan, and France. Moreover, it has been found that over the past 20 years, Japan and France have been clear leaders in the world ranking. Thus, an analysis of the results of the Japanese national team's performances in 2024 showed that 83 medals of various kinds were won during this time. The results of the French national team's performances in 2024 show that 136 medals of various kinds were won during this time, which is 53 medals more than the Japanese team. The results of the Azerbaijani national team's performances in 2024 show that it won 33 medals of various types, which is much less than the teams of Japan and France. The largest number of medals were won at the Grand Slam competitions by representatives of all countries, where rating points and a large prize pool are played.
Keywords: judo; Olympic Games; participants; analysis; results; medal standings